The easiest way to show you how to tackle these type of problems is by working out an example. The basic idea is to get the x-terms on one side of the equation and the constants on the other.

**Example:** Solve:

-8(6x + 5) = 3(8x + 1) + 173

**Step 1:** Get rid of the brackets using the distributive law. We get:

-8(6x + 5) = 3(8x + 1) + 173

-48x - 40 = 24x + 3 + 173

-48x - 40 = 24x + 176

**Step 2:** Get the x-terms on one side of the equation and the
constants on the other side. First we subtract 24x from both sides:

-48x - 40 = 24x + 176

-48x - 40 - 24x = 24x + 176 - 24x

-72x - 40 = 176

Then add 40 to both sides:

-72x - 40 = 176

-72x - 40 + 40 = 176 + 40

-72x = 216

**Step 4:** Divide both sides by -72.

-72x = 216

-72x/-72 = 216/-72

x = -3

Our answer is -3.

**DON'T FORGET!** If you have
something like 2x + 3 -(x + 5), this means
the same thing as 2x + 3 -1(x + 5). So,
when you expand this expression, you get
2x + 3 - 1x - 5
= 1x - 2
= x - 2

Basic add/subtract solve for x

Basic multiply/divide solve for x

Basic add/multiply mixtures

Solving basic problems involving brackets

What is cross-multiplying?

What is the quadratic formula?

Strategy for solving quadratic problems

Solving quadratic problems involving brackets

Solving quadratic problems involving fractions

Basic multiply/divide solve for x

Basic add/multiply mixtures

Solving basic problems involving brackets

What is cross-multiplying?

What is the quadratic formula?

Strategy for solving quadratic problems

Solving quadratic problems involving brackets

Solving quadratic problems involving fractions

Copyright © 2011 - Mathwizz.com all rights reserved